Microparticles: new light shed on the understanding of venous thromboembolism - Zhou, Lin (Nature Publishing Group, 2014)
Microparticles are small membrane fragments shed primarily from blood and endothelial cells during either activation or apoptosis. There is mounting evidence suggesting that microparticles perform a large array of biological functions and contribute to various diseases. Of these disease processes, a significant link has been established between microparticles and venous thromboembolism. Advances in research on the role of microparticles in thrombosis have yielded crucial insights into possible mechanisms, diagnoses and therapeutic targets of venous thromboembolism. In this review, we discuss the definition and properties of microparticles and venous thromboembolism, provide a synopsis of the evidence detailing the contributions of microparticles to venous thromboembolism, and propose potential mechanisms, by which venous thromboembolism occurs. Moreover, we illustrate a possible role of microparticles in cancer-related venous thromboembolism.